2021
DOI: 10.1111/sltb.12756
|View full text |Cite
|
Sign up to set email alerts
|

More frequent negative social exchanges are associated with higher suicide ideation and risk in men service members/veterans

Abstract: Introduction Suicide is a leading cause of death in military service members/veterans (SM/Vs). Positive social exchanges (e.g., emotional support) buffer against suicide risk but the influence of negative social exchanges (e.g., unwanted advice) is understudied. Method The current study explored (1) the contributions of positive and negative social exchanges as simultaneous correlates of suicide ideation and risk, (2) whether positive social exchanges mitigated the association of negative social exchanges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In this study, we used a continuous measure of current SI levels, derived from Item 2, which taps the frequency of current suicidal ideation (“How often have you thought about killing yourself in the past year?”) on a variable 5-point Likert-type scale, ranging from 1 ( never ) to 5 ( very often ; 5 times or more). Other studies have employed a single item to assess suicidality, such as Item 2 of the SBQ-R, to assess SI (Blais et al, 2021; Levi-Belz & Zerach, 2018; Schwartz et al., 2021). Moreover, substantial evidence supports the predictive ability of a single item and its relevance for assessing suicidality (Green et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used a continuous measure of current SI levels, derived from Item 2, which taps the frequency of current suicidal ideation (“How often have you thought about killing yourself in the past year?”) on a variable 5-point Likert-type scale, ranging from 1 ( never ) to 5 ( very often ; 5 times or more). Other studies have employed a single item to assess suicidality, such as Item 2 of the SBQ-R, to assess SI (Blais et al, 2021; Levi-Belz & Zerach, 2018; Schwartz et al., 2021). Moreover, substantial evidence supports the predictive ability of a single item and its relevance for assessing suicidality (Green et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…on a variable 5point Likert-type scale, ranging from 1 (never) to 5 (very often; 5 times or more). Other studies have employed a single item to assess suicidality, such as Item 2 of the SBQ-R, to assess SI (Blais et al, 2021;Schwartz et al, 2021). Moreover, substantial evidence supports the predictive ability of a single item and its relevance for assessing suicidality (Green et al, 2015).…”
Section: Suicidal Behaviors Questionnaire-revisedmentioning
confidence: 99%
“…Interactions characterized by NSE are associated with a range of negative physical health symptoms and mental health outcomes, including depression and loneliness (Tsai et al , 2019), PTSD symptom severity (Blais and Zalta, 2023), drug cravings among recovering opioid users (Knapp et al , 2021) and NSE may even impact the rate of symptoms change in cognitive behavioral therapy for depression (Eidelman et al , 2018). Unfortunately, there is a paucity of research examining the role of NSE as a contributor to suicidal thoughts and behaviors (Blais et al , 2021).…”
Section: Negative Social Exchange As a Contributor To Suicidal Ideationmentioning
confidence: 99%
“…In the limited literature investigating this relationship, NSE have been positively correlated with suicidal thoughts and behaviors in college students, veterans and adults (Blais et al , 2021; Hirsch and Barton, 2011; Lincoln et al , 2012). One study demonstrated that NSE were positively associated with suicidal thoughts and behaviors in college students such that those who reported a greater experience with NSE reported higher levels of SI and suicidal behaviors.…”
Section: Negative Social Exchange As a Contributor To Suicidal Ideationmentioning
confidence: 99%
See 1 more Smart Citation